Cardiac pain at rest. Management and follow-up of 100 consecutive cases. Issue 1 (January 1981) - Brooks, N; Warnes, C; Cattell, M; Balcon, R; Honey, M; Layton, C; Sturridge, M; Wright, J
Abstract : One hundred consecutive patients, admitted to the coronary care unit with cardiac pain at rest but no evidence of recent myocardial infarction have been followed up for nine to 26 (mean 14) months. They were treated initially with bed rest, beta-adrenergic blockade, and nitrates. In 54 patients pain subsided within 24 hours. Coronary angiography was carried out in 46. Thirty-five had coronary artery lesions and three had spasm in normal coronary arteries. One had hypertrophic cardiomyopathy and seven had normal findings. Seventeen patients with previous angina and severe coronary disease were operated on, with one death and one perioperative infarction; two died late, 12 were symptom free, and two had angina. Seven of 18 patients treated medically had recurrent angina and underwent operation. Of the 11 unoperated patients, one died, three had angina, and seven were symptom free. Two of the eight patients who were not catheterised developed infarction, four had angina, and three were symptom free. Recurrent pain continued for more than 24 hours in 46 patients, and all underwent angiography. Forty-three had coronary artery disease and 34 underwent early bypass surgery; there were two operative deaths and three perioperative infarctions. Twenty-six symptom free at follow-up. Of the nine unoperated patients with coronary disease, four developed infarction, two were operated on for recurrent angina, two were symptom free, and one had mild angina. Optimal management of patients with pain at rest can be determined only with knowledge of the coronary artery anatomy and of left ventricular function. Many respond initially to intensive medical treatment and coronary angiography can be performed electively. In those with continuing pain, urgent angiography is required and can be done safely.